Baicalin inhibits human osteosarcoma cells invasion, metastasis, and anoikis resistance by suppressing the transforming growth factor-β1-induced epithelial-to-mesenchymal transition. Issue 6 (July 2017) - Wang, Yanmao; Wang, Huimin; Zhou, Runhua; Zhong, Wanrun; Lu, Shengdi; Ma, Zhongliang; Chai, Yimin
Abstract : The epithelial–mesenchymal transition (EMT) plays an important role in inducing cancer metastasis. Baicalin, a flavone derivative isolated from Scutellaria spp., shows a series of pharmacological and physiological activities. However, the possible role of baicalin in the EMT is unclear. In this study, we attempted to investigate the potential use of baicalin as an inhibitor of transforming growth factor-β1 (TGF-β1)-induced EMT in U2OS cells. We found that TGF-β1 induced the EMT to promote U2OS cells migration, invasion, and anoikis resistance. Western blotting showed that baicalin inhibited U2OS cells' invasion and migration, increased the expression of the epithelial phenotype marker E-cadherin, repressed the expression of the mesenchymal phenotype marker vimentin, as well as decreased the level of EMT-inducing transcription factors Snail1 and Slug during the initiation of TGF-β1-induced EMT. Baicalin also inhibited the TGF-β1-induced increase in cell migration, invasion, and anoikis resistance in TGF-β1-induced U2OS cells. In addition, the TGF-β1-mediated phosphorylated levels of Smad2/3 were inhibited by baicalin pretreatment. Above all, we conclude that baicalin suppresses human osteosarcoma cells' migration, invasion, and anoikis resistance in vitro through suppression of TGF-β1-induced EMT.